Green advertising is more environmentally friendly? The influence of advertising color on consumers’ preferences for green products - Wenting, Feng; Yuelong, Zeng; Xianyun, Shen; Chenling, Liu (Frontiers in Psychology, 2022)
The color of green product advertisements is an important factor affecting consumers’ product preferences. Based on the theory of the self-control system, this paper explores the influence mechanism and boundary conditions of green product advertising color on consumer product preference through three experiments. Experiment 1 tested the effect of advertisement color type (green/color) on consumers' preference for green products. The results show that color ads can promote consumers' preference for green products compared with green ads. At the same time, experiment 1 analyzed the mediating role of the self-control system between advertisement color type (green/color) and consumer preference. Experiment 2 further clarified the boundary of the main effect, namely, the effect of advertising color (green/color) on consumer preference was only effective in the context of green products. Experiment 3 explored the moderating effect of green product type (egoistic/altruistic) on the main effect. The results show that only when the green product type is altruistic, can the advertising color type (green/color) significantly affect consumers' green product preference.